2012
DOI: 10.1302/0301-620x.94b11.30834
|View full text |Cite
|
Sign up to set email alerts
|

Patient specific cutting blocks are currently of no proven value

Abstract: Patient specific cutting guides generated by preoperative Magnetic Resonance Imaging (MRI) of the patient's extremity have been proposed as a method of improving the consistency of Total Knee Arthroplasty (TKA) alignment and adding efficiency to the operative procedure. The cost of this option was evaluated by quantifying the savings from decreased operative time and instrument processing costs compared to the additional cost of the MRI and the guide. Coronal plane alignment was measured in an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
154
2
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(168 citation statements)
references
References 8 publications
5
154
2
7
Order By: Relevance
“…Although Noble et al [24] noted a decrease in operative times with the use of CCGs by 7 minutes, Hamilton et al [17] found the use of traditional instrumentation to be shorter than CCGs by 4 minutes. In addition, the results of several Level II and Level II studies have also been mixed to this regard [6,8,11,25]. No difference in either tourniquet time or total operative time was seen in our study.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…Although Noble et al [24] noted a decrease in operative times with the use of CCGs by 7 minutes, Hamilton et al [17] found the use of traditional instrumentation to be shorter than CCGs by 4 minutes. In addition, the results of several Level II and Level II studies have also been mixed to this regard [6,8,11,25]. No difference in either tourniquet time or total operative time was seen in our study.…”
Section: Discussioncontrasting
confidence: 46%
“…Occasionally, seating of the CCGs was difficult, and thus surgeons took an increased amount of time to confirm that the blocks were seated correctly. Furthermore, a prior cost-analysis study showed any potential savings in operating room efficiency would be greatly outweighed by the current cost of the preoperative MRI and cutting guide fabrication (approximately USD 1500) [6]. Thus, because no difference in surgical times nor radiologic outcomes was noted in our study, the potential financial benefits of improved surgical efficiency and accuracy may not be realized with the use of CCGs [33,39].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The work of Parratte et al [3] suggests that a neutral mechanical axis may not be necessary for longevity in TKA. The inability to complete surgeries using patient-specific guides remains an issue, particularly given the cost for imaging and creation of the guides [1]. While we trust the judgment of an experienced surgeon in abandoning the approach, we ask whether the apparent rotational malalignment determined visually by comparison to gap balancing was an accurate reflection of a true mismatch (the appearance of a trapezoidal flexion space), or whether the guide represented the CT derived ''true'' alignment of the knee?…”
Section: Where Do We Need To Go?mentioning
confidence: 99%